Electropharmacological profile of an atrial-selective sodium channel blocker acehytisine assessed in the isoflurane-anesthetized guinea-pig model - Xin Cao; Yoshinobu Nagasawa; Chengshun Zhang; Hanxiao Zhang; Megumi Aimoto; Akira Takahara (Elsevier, 2019)
Experimental evidence regarding the risk of proarrhythmic potential of acehytisine is limited. We assessed its electropharmacological effect together with proarrhythmic potential at intravenous doses of 4 and 10 mg/kg (n = 6) using isoflurane-anesthetized guinea pigs in comparison with that of bepridil at 1 and 3 mg/kg, intravenously (n = 6). Acehytisine at therapeutic dose (4 mg/kg) decreased the heart rate, prolonged P wave duration, QRS width, QT interval, QTc, MAP90(sinus), MAP90(CL300) and MAP90(CL250). At supratherapeutic dose (10 mg/kg), it prolonged the PR interval besides enhancing the changes induced by the therapeutic dose. Quantitative assessment showed that peak changes in P wave duration by acehytisine at 10 mg/kg were 1.7 times longer than bepridil, and in MAP90(sinus), MAP90(CL300) and MAP90(CL250) by acehytisine were 1.9, 1.5 and 1.5 times shorter than bepridil, respectively. Importantly, qualitative assessment indicated that bepridil increased beat-to-beat variability and J-Tpeakc in a dose-related manner, confirming a higher proarrhythmic risk, whereas such dose-related responses were not observed in acehytisine, suggesting a lower proarrhythmic risk. These results suggest that acehytisine exhibits favorable pharmacological characters, i.e. potent atrial inhibition and lower proarrhythmic toxicity compared with bepridil, being a promising candidate for the treatment of paroxysmal supraventricular tachycardia. Keywords: Acehytisine, QT prolongation, Proarrhythmic potential, Early repolarization, Short-term variability